11‐2: Student Paper: High Brightness and Ultra‐High PPI Field‐Sequential‐Color (FSC) Display Based on Deformed Helix Ferroelectric Liquid Crystal for VR/AR. Issue 1 (28th June 2022) - SUN, Zhibo; WANG, Sisi; YUAN, Zhengnan; XIA, Zhihe; LU, Lei; WONG, Man; KWOK, Hoi-Sing; SRIVASTAVA, Abhishek Kumar
Abstract : Different display‐based technologies like LCD, OLED and LED, all meet barriers in increasing brightness and pixel density. In this paper, a defect‐free high‐contrast fast (~100 μs) active‐matrix addressed DHFLC is proposed with a theoretical 11500 PPI due to its nature of no fringe field effect (FFE) and high capacitance, shedding a light on the barriers. For the realization, the no‐storage‐capacitor AM‐DHFLC display device is fabricated as a preliminary demo with both optimizations in the DHFLC alignment and pixel design. Innovatively, the no‐storage‐capacitor characteristic, which is impossible for NLC, not only rockets efficiency and aperture ratio from 57 % to 83 % with high brightness, but also reveals the potential in reducing the pixel size for higher resolution. Moreover, a fast response around 100 μs at 360 Hz for FSC display and no‐FFE strengthens the promising potential of DHFLC in various modern display technologies, be it VR/AR, high PPI display, microdisplay, and high‐resolution hologram.